Improving Indonesian History Learning Outcomes through the Application of Directed Teaching Models - Asrida Asrida (Pinisi Journal of Education and Management, 2022)
Guided Teaching Model is a form of learning that requires teachers to ask one or more questions to track students' knowledge or get their hypotheses or conclusions. The purpose of this study is to describe the application of the Guided Teaching Model so that it can improve learning outcomes of Indonesian History in class XI MIPA 1 SMA Negeri 3 Sigi in the odd semester of the 2021/2022 academic year. This research is a classroom action research. The research subjects are students of class XI MIPA 1 SMA Negeri 3 Sigi in the odd semester of the academic year 2021/2022 with a total of 18 people, which is 50% of the number of students in the class. While the research procedure consists of 4 stages, namely: planning, implementation, observation, and reflection. Furthermore, data analysis was carried out through three stages, namely data reduction, data presentation, and data verification/conclusion. The results showed that the application of the directed teaching model could improve the learning outcomes of Indonesian History in class XI MIPA 1 SMA Negeri 3 Sigi in the odd semester of the 2021/2022 academic year.